Camera Security System on Train Station - Chumsit, Suphot; Sukphon, Chomphunut; Charoenprakop, Akyanattha; Ketchum, Mahasak (Science Technology and Innovation Journal, 2020)
This research aims to propose the image enhancement method using and Matching Data with Histogram Shapes technique. The experiments were conducted using images with 1,280 x 720 pixel from CCTV surveillance video system. Type of images (-jpg) isRGB24 form first frame' s surveillance video file (avi.) .The results showed that the proposed method using images Enhancement technique can be used to improve quality of images from surveillance video system. Then using Histogram Shapes technic to matching data can be alert suddenly.